BLACKSPOT IDENTIFICATION USING AEK AND BKA METHODS ON NATIONAL ROAD IN JAVA ISLAND - Shinta Novriani (University Of Muhammadiyah Jakarta, 2021)
Traffic accidents tend to increase and are still the main problem in the implementation of road transportation in Indonesia, especially on the island of Java. Based on the results of the population census, in 2016, 2017 and 2018 the average population on the island of Java reached 148 million people. As much as 56.1% of the total population in Indonesia is concentrated on the island of Java. This has an impact on increasing mobilization and the need for transportation so that traffic accidents tend to increase. Based on secondary data from the Korlantas Polri, the number of accidents increased by 5% from 2016 to 2018. The lack of handling and repairs in traffic accident-prone locations is one of the causes of frequent traffic accidents. Therefore, greater attention is needed on locations where traffic accidents often occur in order to reduce the number of traffic accidents every year. This study aims to identify LRK on national roads in Java with a frequency of 2 events per year, analyze the characteristics of accidents using the Accident Equivalent Rate and Upper Control Limit method. Data on victims of Death (D), Serious Injury (SI), Minor Injury (MI) and Material Losses (ML) in 2016, 2017 and 2018 were obtained from the Korlantas Polri. Based on these data, the AEK value is calculated and analyzed to obtain LRK using the BKA method. The results of the analysis show that the total LRK in Java is 1301 LRK in 2016, 1278 LRK in 2017 and 1309 LRK in 2018 so that there are 1296 LRK on average per year. Analysis of traffic accident data using the AEK and BKA methods in 2016 obtained the highest AEK value found in the province of East Java with an AEK value of 277024 events; Central Java with an AEK value of 183813 events and West Java with an AEK value of 139677 events, therefore there are 3 provinces with the highest number of Accident Prone Location (LRK) in Java, namely East Java, Central Java and West Java.